Cross store research on the shopping convenience. - Neo, Xiaomin. (2008)
This study seeks to establish the relationship between the various dimensions of convenience, consumers’ satisfaction, repurchase intentions and recommendation. The dimensions of convenience investigated are Decision, Access, Transaction, Benefit, and Post-benefit convenience, as proposed by prior studies. Primary research is done through literature review of the concepts of convenience and related topics, and secondary data collection done via surveys conducted to obtain the local consumers’ perceptions regarding this subject in relations to their preferred convenience stores. We compared 7-Eleven, Cheers and I-Econs on consumers’ perceptions of their provision of convenience. The relationship between the various dimensions and overall convenience is also proposed and tested, with time pressure and impulsivity as control factors. Statistical analyses conducted on the data shows that there is a positive relationship between convenience and consumers’ satisfaction. Satisfaction is also positively related to repurchase intention and recommendation. Armed with the results, retailers can more confidently invest in improving convenience as it is shown to be closely related to the bottom-line. They can also be more in tuned to the needs of the local consumers with regards to convenience.